Evaluation of Pharmacokinetical Parameters of Phenol, a Component of Antiseptic Dorogov's stimulator 3 Fraction Paste - V. I. Nozdrin; G. A. Piavchenko; M. E. Ivanova; K. S. Guzev; S. L. Kuznetsov (Разработка и регистрация лекарственных средств)
Introduction. Antiseptic Dorogov's stimulator 3rd fraction (ASD-3) is a multicomponent substance, which is obtained by the thermal processing of cattle-origin tissues, which contains more than 120 substances, including biologically active substances. Among the components of ASD-3, necessary for quantitative analysis, pyrrole, phenol, cresol and its derivatives, and indole are distinguished as components. Despite the fact that antiseptic Dorogov's stimulator 3rd fraction was discovered more than half a century ago, there is no information about the pharmacokinetics of the drug components to date. Phenol is one of the preferred substances for research because that is a substance applied in the pharmaceutical technology for the manufacture of medicines.Aim. Study of pharmacokinetic parameters of phenol as a component of a drug containing an antiseptic Dorogov's stimulator 3rd fraction in a dose of 0.5 g/kg, with a single use in a blood serum of 84 female rats weighing 100–120 g.Materials and methods. In the blood serum of the 84 female Wistar rats weighing 100–120 g a study of a phenol pharmacokinetics as a component of ASD-3 drug in a dose of 0.5 g/kg was performed by a single skin application. The first group of animals was intraperitoneally injected with an aqueous emulsion containing 5% ASD-3, while the second one received zinc paste containing 5% ASD-3 on a skin surface. After the application of the emulsion or paste, the animals were euthanized after 0.25; 0.5; 1; 1.5; 2; 6 and 8 hours with further collection of blood from the abdominal aorta into centrifuge tubes. The study was carried out by high performance liquid chromatography.Results and discussion. The elimination rate constant for intraperitoneal drug emulsion injection is 0,0968 h-1, and when the drug paste is applied, 0.0581 h-1. As a result, the half-life of phenol in the first case is 7.2 hours, and in the second case – 11.9 hours. The relative bioavailability of the phenol from the paste containing 5% of the ASD-3 is 14.38% to the 5% emulsion injected into the rats body intraperitoneally.Conclusion. Comparison of the phenol concentration in the blood serum of experimental animals in two ways of application showed that the skin application of a drug paste containing 5% of ASD-3 provides a 10 times lower content of phenol in the blood serum compared to the intraperitoneal application of an emulsion with 5% ASD-3. 15 minutes after the skin application, the components of the drug start to be detected in the blood serum, reaching its maximum concentration in 1.5–2 hours, subsequently gradually decreasing.